2006
DOI: 10.17221/2689-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bt-maize on epigeic spiders (Araneae) and harvestmen (Opiliones)

Abstract: The effect of two strategies, used to control <i>Ostrinia nubialis</i>, on the abundance and diversity of epigeic spiders and harvestmen in maize was monitored. The two strategies were (1) transgenic insect-resistant maize, and (2) biological control by <i>Trichogramma</i> wasps on an isogenic maize hybrid. They were compared with a conventional system (isogenic maize hybrid), which was taken as the control. The investigation was performed at two localities (Ivanovice na Hané and Prague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Species composition in our study was similar to that reported by Řezáč et al. (); 28 species reported by these authors were also present in our collections.…”
Section: Discussionsupporting
confidence: 92%
“…Species composition in our study was similar to that reported by Řezáč et al. (); 28 species reported by these authors were also present in our collections.…”
Section: Discussionsupporting
confidence: 92%
“…This species is very rare in the Czech Republic (Buchar & Růžička, 2002), but it has also been reported previously in the monitored area (Horáková 2005;Niedobová at al., 2011). In the Czech Republic, this species was fi rst recorded by Miller (1974) from beet fi elds, and other published fi ndings of this species come from fi elds as well (Roberts 1987(Roberts , 1995Řezáč et al, 2006;Öberg et al, 2008;British Arachnological Society, 2011). We believe that it is unreasonable to include this species in the Red List of invertebrates of the Czech Republic (Růžička, 2005) at all, it is very rare species although common habitats like arable fi elds and it is impossible to manage or protect habitats according to its presence.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is evidence on spider abundance in GE vs. conventional crops from field experiments. A number of European studies have reported no difference in the spider community in lepidopteran‐active, Cry1Ab‐expressing Bt maize vs. conventional maize fields (Volkmar and Freier, 2003; Meissle and Lang, 2005; Ludy and Lang, 2006b; Řezáč et al ., 2006; Toschki et al ., 2007). For corn rootworm‐resistant, Cry3Bb1‐expressing maize, however, few field data on spider communities are available and no details for different spider families have been published (Meissle and Romeis, 2008).…”
Section: Introductionmentioning
confidence: 99%